Converse flexoelectricity around ferroelectric domain walls. (1st June 2020) - Wang, Y.J.; Tang, Y.L.; Zhu, Y.L.; Feng, Y.P.; Ma, X.L.
Abstract: Converse flexoelectricity is the mechanical strain induced by electric polarization gradients, which is largely omitted compared with the relatively well-known direct flexoelectricity. Thoroughly understanding the converse effect may not only explain peculiar structures generated by electric polarization or field gradients, but also stimulate new ideas to the design of novel electromechanical devices. In this work, the converse flexoelectricity around ferroelectric domain walls has been studied elaborately by synergetically integrating the aberration-corrected transmission electron microscope (TEM), first-principles calculations, and the Landau-Ginzburg-Devonshire (LGD) theory, taking prototypical tetragonal ferroelectric PbTiO3 as an example. We not only uncovered the important role of converse flexoelectricity on the asymmetric structure around 90° domain walls, but also quantified the flexoelectric coefficients. This quantification is deterministic in both the magnitude and sign of flexoelectric coefficients, by the mutual verification of the atomic mapping and first-principles calculations. Our results suggest that the converse flexoelectricity cannot be neglected for understanding ferroelectric DWs and other boundaries in ferroelectric materials. Graphical abstract: Image, graphical abstract